A Veblenian Approach to Chaos Theory - Isaiah Henry (Hatfield Graduate Journal of Public Affairs)
This paper provides a comparative analysis of Veblen's belief in disequilibrium, the field of chaos theory, and how these two frameworks connect. We explore the similarities and differences between Veblen's theories and the principles of chaos theory, including their shared emphasis on complexity and unpredictability. By analyzing the connections between Veblen's economic theories and chaos theory, we can gain a deeper understanding of the nature of disequilibrium and the complex forces that shape our world.